Accessibility and Modernization: Modern Islam Surau In Nagari Kurai Taji Pariaman 1912-1930 - Fikrul Hanif Sufyan; Zusneli Zubir (Criksetra: Jurnal Pendidikan Sejarah, 2023)
This article aims to analyze modernization in Kurai Taji, explain the influence of modernist Islam on Kurai Taji, and find the causes of the famine and its handling in 1939. This paper is based on historical methods, namely heuristics, criticism, interpretation, and historiography. The presence of the railway in Nagari Kurai Taji had a major influence in encouraging the presence of formal schools, the high interest of the surrounding nagari to attend school in Kurai Taji, including in the growth of modernist Islam. Uniquely, in Kurai Taji, the modernist Islamic movement started from a surau – a traditional Minangkabau-style education system that built religious networks and bases. The two surau that contributed the most to the spread of the Youth Movement in Kurai Taji were the Paninjauan Surau and the Dagang Surau. The rapid growth of the modernist Islamic movement and Muhammadiyah cannot be separated from the role of copra traders and the accessibility of rail transportation modes.